Photo‐Modification of Melanin by a Mid‐infrared Free‐electron Laser. (7th February 2019) - Kawasaki, Takayasu; Sato, Aomi; Tominaga, Yuki; Suzuki, You; Oyama, Takahiro; Tadokoro, Makoto; Tsukiyama, Koichi; Nokihara, Kiyoshi; Zen, Heishun
Abstract: Melanin is rigidly constructed by several nitrogen‐containing aromatic rings, and its excess accumulation in skin tissue is closely associated with melanosis. Although visible lasers (wavelength: 600–1000 nm) are conventionally used for the photo‐thermolysis of melanocyte, several pigmented nevi are difficult to be treated. Here, we propose an alternate method for targeting the molecular structure of melanin using an infrared free‐electron laser (FEL) tuned to 5.8 μm that corresponds to the stretching vibrational mode of carboxylate group. A drastic morphological change on the black‐colored surface of melanin powder was observed after the pulse irradiation with power energy of 500 mJ cm −2, and the minimum irradiation time for damage to the morphology was 1.4 s. Analyses by mass spectroscopy, infrared spectroscopy, and 13 C‐nuclear magnetic resonance implied that a pyrrole group was removed by the FEL irradiation. In addition, the FEL irradiation dispersed almost all of the melanoma cells from a culture solution without any influence on other ingredients in the medium, and one‐cell analysis by infrared microscopy showed that the structure of melanoma could be substantially damaged by the irradiation. This study proposes the potency of intense mid‐infrared laser as novel alternative way to reduce melanin. Abstract : We applied a free‐electron laser tuned to mid‐infrared wavelength (5.8 μm) to irradiate melanin. The melanin powder was dispersed by the pulse irradiation with power energy of 500 mJ cm −2, and the minimum pulse number for damage to the morphology of melanin was 2 macro‐pulses, which was equivalent to 1.4 s of irradiation. Analyses by mass spectroscopy, infrared spectroscopy, and 13 C‐nuclear magnetic resonance implied that pyrrole group in the structure of synthetic melanin was dissociated by the FEL irradiation. In addition, melanoma cells were substantially damaged by FEL irradiation.